Doomscrolling behavior and learning concentration among junior high school students: A correlational study with implications for school counseling - Yuliskhana Yuliskhana; Adi Atmoko; Fitri Wahyuni; Augusto da Costa (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2026)
Doomscrolling refers to the tendency to continuously scroll through and consume negative digital information, a behavior that may interfere with adolescents' emotional readiness and academic attention. Despite the growing number of studies on digital media and adolescent well-being, limited evidence has examined doomscrolling in relation to learning concentration among junior high school students. This study aimed to examine the relationship between doomscrolling behavior and learning concentration and to formulate implications for school counseling. A quantitative correlational design was employed with 112 eighth-grade students of SMP Negeri 2 Gurah, Indonesia. Data were collected using a 20-item doomscrolling behavior questionnaire and a 20-item learning concentration questionnaire. Instrument quality was examined using corrected item-total correlation and Cronbach's alpha. Descriptive statistics, normality and linearity tests, and Spearman's rank correlation were used for data analysis. Instrument evaluation indicated that all items met the validity criterion, with corrected item-total correlation values ranging from .305 to .736 for doomscrolling behavior and from .335 to .682 for learning concentration. Both scales demonstrated excellent reliability, with Cronbach's alpha values of .919 and .916, respectively. Spearman's correlation analysis revealed a significant negative relationship between doomscrolling behavior and learning concentration, rho = -.360, p < .001. These findings indicate that higher doomscrolling tendencies are associated with lower learning concentration. The study highlights the need for school counseling services that promote digital self-regulation, healthy information consumption, and learning concentration strategies among junior high school students.